Value pluralism, trade-offs and efficiencies - Nikolai Hoberg; Stefan Baumgärtner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
Political decision-makers face increasing demands to justify their actions with respect to multiple normative objectives or values. Here, we provide a general philosophical-economic clarification of the discussion of value pluralism, value-efficiency (i.e. efficiency with respect to values) and feasible relationships between values. We derive what relationships between values can exist in states of affairs that are valueefficient. In particular, we show that in a value-efficient state of affairs there is a tradeoff between at least two values, and that a win-win relationship between values is no indication of value-inefficiency when there are three or more values. Further, we connect these relationships to the opportunity costs of attaining a value to a higher degree. Lastly, we contrast Pareto-efficiency with value-efficiency and show that there can be a win-win relationship between values in a Pareto-efficient state of affairs. Our analysis provides insights that help decision-making in situations where there are multiple values at stake.
Keywords: D63; H43; H00; 330; efficiency; value pluralism; value trade-offs; welfarism